iStent inject trabecular microbypass stent implantation with cataract extraction in open-angle glaucoma: early clinical experience - Ferguson, Tanner J. (Eye Vis (Lond), 2020)
BACKGROUND: Retrospective, consecutive case series to evaluate the implantation of two second-generation trabecular microbypass stents in combination with cataract surgery in a real-world, clinical setting. METHODS: The series included 56 eyes implanted with the iStent inject device with phacoemulsification. The series consisted of eyes with primary open-angle glaucoma (n = 52) and pseudoexfoliative glaucoma (n = 4). Primary outcome measures included intraocular pressure (IOP) and number of glaucoma medications. Safety outcomes included the need for secondary surgical intervention and the incidence of IOP spikes ≥10 mmHg and ≥ 15 mmHg. RESULTS: IOP was reduced by 21% to 14.7 ± 2.9 mmHg (p < 0.01) at 6 months postoperative from 18.7 ± 5.8 mmHg at baseline. Preoperatively, the mean number of glaucoma medications was 1.5 ± 0.9 and reduced by 39% to 0.9 ± 1.2 (p < 0.01) at 6 months. At 6 months, 68% of eyes had an IOP ≤15 mmHg, increased from 30% at baseline. 55% of eyes were medication-free at 6 months, up from 18% at baseline. There were no severe postoperative complications. No eyes underwent an additional glaucoma procedure. CONCLUSIONS: Implantation of the iStent inject device with concomitant cataract surgery effectively provides a sustained reduction in IOP with a markedly improved medication burden out to 6 months postoperative. The safety profile is excellent.